Use of bidirectional Mendelian randomization to unveil the association between antibody-mediated immune responses to infectious agents and allergic rhinitis - Wencan Cao; Xiaxuan Chen; Xinrong Li; Yuxian Wang (Human Vaccines & Immunotherapeutics, 2025)
Allergic rhinitis (AR) is increasingly prevalent, yet diagnostic and therapeutic approaches remain inadequate. Recent studies show links between infectious diseases and noninfectious disorders, but the underlying mechanisms are largely unknown. We used bidirectional Mendelian randomization (MR) to investigate the impact of antibodies against infectious diseases on AR. Our results indicate that CMV IgG+, human herpesvirus 7 U14 antibodies, anti-varicella zoster virus IgG (VZV IgG+), and varicella zoster virus glycoproteins E/I antibodies are positively correlated with AR, while Epstein-Barr virus EBNA-1, ZEBRA, Merkel cell polyomavirus VP1, BK polyomavirus VP1, anti-human herpesvirus 6 E1A IgG, and human herpesvirus 6 IE1A antibodies are negatively correlated. Reverse MR analysis shows AR increases VZV IgG+ likelihood. These findings suggest a bidirectional causal relationship between infectious disease immune responses and AR, advancing understanding and potential diagnostics.